INFLUENCE OF SUMMER BREAK AT SOME MOTORIC ABILITIES ON FOOTBALL PLAYERS AGED 10 YEARS OLD - Stevo Popović; Slavko Molnar; Miroslav Smajić (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2010)
There were many researches about the influence of training process to the development of motoric abilities all around the world and in our country, too. However, there were much less researches about the influence of breaks to the development of the same abilities. The object of this research was the influence of summer break to development of motoric abilities to the boys in a football school "RMR Vojvodina". The main goal of this research represented the derivation some knowledge about the influence of summer break to some motoric abilities. Next to the object and main goal of this research, there were some tasks which had to be done to got the main goal: the first task was measurement of some motoric abilities at the end of the training process, then the second task was measurement of same motoric abilities after summer break, then reviewing all attained results and identification the influence of break to development specified motoric abilities. The sample was taken from 40 boys aged 10 years old and the authors used the battery of eight motoric tests as variables (Radosav, Molnar, Smajić, 2003). The data was collected by t-test and it was concluded there were a significant difference of means in three variables.